A SEMANTIC STUDY OF LUCKY DUBE’S SONGS - DIGUMEFELE, Marie-Jeanne NGELEMA; KOLOKOTA, Justin MBULA WA (IJRDO- Journal of Educational Research, 2022)
The present article deals with a semantic study of Lucky Dube’s songs, a musician from South Africa. In fact, a writer does not write only for the pleasure of writing. He can present a fact to teach or instruct people, criticize bad situations, praise important figures, entertain the community, sympathize with miserable individuals, and to name only those. It is the same way with a musician through songs he does likewise, songs and chants being among elements including oral literature facilitating him in transmitting the message. So, we have selected ten of the artist’s songs to analyse in order to sort out the meaning or message conveyed in his lyrics.